2022
DOI: 10.1134/s1064229322050039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Current Risks of Excessive Heavy Metal Accumulation in Soils Based on the Concept of Critical Loads: A Review

Abstract: At the international level, the concept of critical loads developed under the Convention on Long-Range Transboundary Air Pollution directed by the United Nations Economic Commission for Europe is actively used to assess the risks of excessive inputs of pollutants into ecosystems. The review considers the main principles of the concept of critical loads and methods of its application for assessing the current risks of excessive accumulation of heavy metals (HMs) in soil as a component of terrestrial ecosystems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Climate makes a significant contribution to the formation of soil types, and these two factors, climate and soil type, largely dictate the mobility and availability of elements, including metals and metalloids (Nedrich & Burton, 2017;Koptsik & Koptsik, 2022). Arid climates, such as those in the western United States, tend to a low content of organic matter and high carbonate and salt abundances.…”
Section: Conditions Promoting Bioavailability In Soilmentioning
confidence: 99%
“…Climate makes a significant contribution to the formation of soil types, and these two factors, climate and soil type, largely dictate the mobility and availability of elements, including metals and metalloids (Nedrich & Burton, 2017;Koptsik & Koptsik, 2022). Arid climates, such as those in the western United States, tend to a low content of organic matter and high carbonate and salt abundances.…”
Section: Conditions Promoting Bioavailability In Soilmentioning
confidence: 99%
“…Heavy metals availability in terrestrial ecosystems depends on soil characteristics, their physicochemical form, and plant species (Koptsik & Koptsik, 2022). A significant element of nutritional metal acquisition is the exudates released from roots into the rhizosphere through chelator assets.…”
Section: Extracellular Metal Speciationmentioning
confidence: 99%
“…This body of research has consistently reported elevated concentrations of heavy metals in affected areas compared to control sites. For example, studies documented significant accumulations of lead, cadmium, and chromium in soil samples collected from areas adjacent to metal-processing industries (13,14). Similarly, increased levels of mercury and arsenic were found in vegetation near coal-fired power plants, showcasing the widespread impact of industrial emissions on environmental contamination (10,15).…”
Section: Introductionmentioning
confidence: 99%